SOFTWARE TO SUPPORT LOGISTIC DECISION IN THE PROCESS OF ORGAN ACQUISITION AND TRANSPLANTATION. - Martins Costa, Juliana; Schlindwein Meirelles, Betina Hörner; Pestana Magalhães, Aline Lima (Revista Baiana de Enfermagem, 2023)
Objective: to develop and evaluate a software to support the decision-making of transplant center professionals in the logistic definitions involved in the process of organ procurement and distribution for transplantation. Method: applied technological production study, supported by the Design Science Research Methodology method. Ten nurses from the Transplant Center of Santa Catarina participated in the usability evaluation stage. Data collection took place from 1 to 20 July 2021 through the System Usability Scale questionnaire. Results: the software used JavaScript language with ReactJS and PHP with Laravel, for the PostgreSQL database. The evaluation obtained a mean score of 98.25, and its usability is considered as best achievable. Conclusion: the software proved to be adequate and functional, with easy handling, gathering integrated and objective information. It represents a breakthrough in the area, proposing a technological innovation for the management and support to the logistic decisions involved in the process of organ procurement and transplantation.